2022
DOI: 10.35877/454ri.mattawang908
|View full text |Cite
|
Sign up to set email alerts
|

Efforts to Increase Adolescent Knowledge and Awareness About Menstrual Health Management Through the Provision of Health Education in Boarding School

Abstract: Menstrual health management is the management of hygiene and health during menstruation period. Health education about reproductive health is important for adolescent to know, so that they have the correct information and knowledge about the topic. Adolescents who have a poor understanding of genital personal hygiene can cause reproductive health problems such as vaginal discharge and reproductive tract infections. So it is necessary to provide information about reproductive health, especially menstrual hygien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…Likewise, the research of (Wulandari & Prihatin, 2022), As per the study findings, it was observed that a higher proportion of respondents exhibited lower levels of knowledge, namely 44 people (53.7%), while the level of knowledge was only 38 people (46.3%). Most respondents' knowledge is lacking, this is due to the lack of information about nutrition obtained from schools and the surrounding environment.…”
Section: Knowledge About Nutritionsupporting
confidence: 61%
“…Likewise, the research of (Wulandari & Prihatin, 2022), As per the study findings, it was observed that a higher proportion of respondents exhibited lower levels of knowledge, namely 44 people (53.7%), while the level of knowledge was only 38 people (46.3%). Most respondents' knowledge is lacking, this is due to the lack of information about nutrition obtained from schools and the surrounding environment.…”
Section: Knowledge About Nutritionsupporting
confidence: 61%